Controlled release of vancomycin from bone plate via layer-by-layer coating - Norased Nasongkla (2020)
© 2018 IEEE. Bone plate has been successfully used for bone fixation however, implant failures caused by infection often occurred with bacterial exposure. To address this issue, the bone plate was layer-by-layer coated by poly(lactic acid)/vancomycin (PLA/VCM) and also investigated important properties such as drug loading content and drug release. The amount of VCM on the surface after 42 layers of coating was 14, 131, and 350 μg for method A, B, and C, respectively. The coating was able to provide bacterial inhibition for 11, 15, and 15 days for method A, B and C, respectively. PLA/VCM-coated bone plates are the promising approach and will have broad applications in the orthopedic implants.